PENGGUNAAN MEDIA YOUTUBE DALAM MENINGKATKAN MOTIVASI BELAJAR FIQIH MELALUI PEMBELAJARAN DARING MADRASAH ALIYAH NEGERI 2 SITUBONDO - Qodri, Mifta Lailatul (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
This research was conducted to find out, How is the application of using Youtube media in increasing motivation to learn jurisprudence through learning, What are the results of using Youtube media in increasing motivation to learn jurisprudence through online learning and How is the effectiveness of using Youtube media in increasing motivation to learn jurisprudence through online learning in class XI students Madrasah Aliyah Negeri 2 Situbondo. In this study, researchers used a qualitative approach and used a qualitative descriptive research method. Data collection techniques by means of observation (observation), interviews (interviews), and documentation. Based on the research conducted, there are several results that at MAN 2 Situbondo: 1) The application of Youtube media is implemented by means of educators providing material through group chats, then students watch videos of fiqh practice on Youtube according to directions from educators, and finally make practice videos according to the references provided. they have seen on Youtube. Then students upload via group chat with a predetermined time. 2) The results of using Youtube media in increasing motivation to study fiqh are considered successful, and very good because using Youtube media is easier to use, easier to find material, and students are seen as more enthusiastic, not even bored in the learning process. 3) The effectiveness of using Youtube media in fiqh learning, namely students are more enthusiastic in the learning process, before entering new material the educator ensures that students understand the old material, the amount of material and information provided by educators so that students are able to develop their creativity and not only race on a single reference. Educators who give assignments, and students who collect assignments according to a predetermined time, as well as educators who motivate students to study hard for a better future, advise, and criticize if students make mistakes. Keywords: Use of Media Youtube, Motivation to Learn Fiqh, Online Learning Abstrak Penelitian ini dilakukan untuk mengetahui, Bagaimana penerapan penggunaan media Youtube dalam meningkatkan motivasi belajar fiqih melalui pembelajaran , Bagaimana hasil penggunaan media Youtube dalam meningkatkan motivasi belajar fiqih melalui pembelajaran daring dan Bagaimana efektivitas penggunaan media Youtube dalam meningkatkan motivasi belajar fiqih melalui pembelajaran daring pada siswa kelas XI Madrasah Aliyah Negeri 2 Situbondo. Pada penelitian ini peneliti menggunakan pendekatan kualitatif serta menggunakan metode penelitian deskriptif kualitatif. Teknik pengumpulan data dengan cara pengamatan (observasi), wawancara (interview), dan dokumentasi. Berdasarkan penelitian yang dilakukan ada beberapa hasil bahwa di MAN 2 Situbondo: 1) Penerapan media Youtube diterapkan dengan cara pendidik memberikan materi melewati obrolan grup, kemudian peserta didik menonton video praktik fiqih di Youtube sesuai arahan dari pendidik, dan terakhir membuat video praktik sesuai referensi yang telah mereka lihat di Youtube. Kemudian peserta didik mengupload melalui obrolan grup dengan waktu yang telah ditentukan. 2) Hasil dari penggunaan media Youtube dalam meningkatkan motivasi belajar fiqih dinilai berhasil, dan sangat baik karena penggunaan media Youtube lebih mudah digunakan, lebih mudah mencari materi, dan peserta didik dilihat lebih antusias, bahkan tidak jenuh dalam proses pembelajaran. 3) Efektivitas penggunaan media Youtube dalam pembelajaran fiqih, yaitu peserta didik lebih antusias dalam proses pembelajaran, sebelum memasuki materi baru pendidik memastikan terlebih dahulu peserta didik memahami materi yang lama, banyaknya materi dan informasi yang diberikan pendidik agar peserta didik mampu mengembangkan kreatifitasnya dan tidak hanya berpacu pada satu referensi. Pendidik yang memberikan penugasan, dan peserta didik yang mengumpulkan penugasan sesuai dengan waktu yang telah ditentukan, serta pendidik yang memotivasi peserta didik untuk giat belajar demi masa depan yang lebih baik, menasihati, dan mengkritik jika peserta didik melakukan suatu kesalahan.